Hepatic toxicity during regorafenib treatment in patients with metastatic gastrointestinal stromal tumors - Ivanyi, Philipp (Mol Clin Oncol, 2020)
Regorafenib is a multi-target tyrosine kinase inhibitor that has been approved for the treatment of metastatic colorectal cancer, advanced hepatocellular carcinoma, and metastatic gastrointestinal stromal tumors (GIST). Severe hepatobiliary toxicity has been reported in patients with colorectal cancer treated with regorafenib, but not in those with GIST. Therefore, the aim of the present study was to investigate the incidence and clinical course of regorafenib-associated hepatic toxicity (HT) in patients with GIST in a real-world setting. Patients with metastatic GIST treated with regorafenib between September 2012 and May 2014 at three German tertiary care centers were followed up until August 2017. Patient records were retrospectively analyzed and descriptive statistics were employed. HT was defined as alterations in the serum values of aspartate aminotransferase, alanine aminotransferase, γ-glutamyltransferase, alkaline phosphatase and bilirubin (according to the Common Terminology Criteria for Adverse Events, version 4.0), and/or corresponding clinical signs. The time to clinical progression and the overall survival were calculated by Kaplan-Meier curves. Overall, 21 patients were treated with regorafenib and 5 (23.5%) of those heavily pretreated patients suffered from severe HT during regorafenib treatment. In 4 (80%) of these cases, regorafenib treatment was continued, optimizing individual treatment benefit. Clinical monitoring and adequate therapy management are crucial for ensuring continuation of regorafenib treatment in order to achieve an optimal clinical outcome.